Desenvolvimento de leite de cabra fermentado adicionado de cepas probióticas, inulina, amido e gelatina - Garcia, Rita Vieira (2011)
The dairy sector is seeking to produce foods with functionality as main attribute. In this context, a market to be explored is that of dairy goats, since goat milk is a food alternative of excellent dietary and nutritional characteristics. However, due to its physical and chemical characteristics, the milk produces a soft clot after fermentation, giving a product with poor texture. The objective of this study was to develop a goat milk fermented by the action of probiotic strains Lactobacillus acidophilus LA-5, Bifidobacterium BB-12 and Streptococcus thermophilus added of the prebiotic ingredient inulin and thickeners starch and gelatin and to evaluate its physicochemical composition susceptibility to syneresis, bacterial counts and sensory analysis on the first day of preparation and after 15 days of refrigerated storage. The tests were elaborated according to a factorial experimental design with three levels and three central points totaling eleven trials. The minimum and maximum levels were selected based on legal limits, literature data and preliminary tests considering the sensory quality evaluated by tasters. Starch, gelatin and inulin represented the variable ingredients and the fixed ingredients were: milk powder, sugar, milk and yeast. The process steps were milk weighing, mix preparation, heat treatment, cooling, direct inoculation, incubation, cooling, clot breaking, filling and storage. The developed formulations met the legal requirements for fermented milk regarding protein, fat and acidity average values. The starch and gelatin levels, combinations and interaction with inulin were sufficient to promote a significant decrease in the serum separation rate. Most formulations reached the minimum number of microorganisms required by legislation for fermented milk. The sensory properties appearance, color and consistency achieved high scores and aroma and flavor scored around five. In general, no significant changes were observed in the counts of probiotic bacteria and sensory quality of the newly developed formulations in relation to formulations after 15 days of refrigerated storage. The addition of probiotic bacteria and prebiotic ingredient inulin improved the potential of goat milk to provide beneficial effects to human health.